An aging pathway controls the TrkA to p75(NTR) receptor switch and amyloid β-peptide generation - Costantini, Claudio (2006)
Aging of the brain is characterized by marked changes in the expression levels of the neurotrophin receptors, TrkA and p75(NTR). An expression pattern in which TrkA predominates in younger animals switches to one in which p75(NTR) predominates in older animals. This TrkA-to-p75(NTR) switch is accompanied by activation of the second messenger ceramide, stabilization of β-site amyloid precursor protein-cleaving enzyme-1 (BACE1), and increased production of amyloid β-peptide (Aβ). Here, we show that the insulin-like growth factor-1 receptor (IGF1-R), the common regulator of lifespan and age-related events in many different organisms, is responsible for the TrkA-to-p75(NTR) switch in both human neuroblastoma cell lines and primary neurons from mouse brain. The signaling pathway that controls the level of TrkA and p75(NTR) downstream of the IGF1-R requires IRS2, PIP3/Akt, and is under the control of PTEN and p44, the short isoform of p53. We also show that hyperactivation of IGF1-R signaling in p44 transgenic animals, which show an accelerated form of aging, is characterized by early TrkA-to-p75(NTR) switch and increased production of Aβ in the brain.